2016
DOI: 10.21837/pmjournal.v14.i4.166
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Implementation and Success of Green Urban Mobility in Asian Cities

Abstract: Urban population is rapidly increasing at the rate of 1.83% worldwide. This is accompanied by rise in auto-mobile ownership, which conversely imposes adverse environmental, health, economic and social impact in cities. Green Mobility has emerged as the best approach for promoting sustainable and environmental-friendly transportation in modern cities. This paper relied on secondary data to critically review current transport problems, efforts toward ensuring sustainable green mobility, success of the policies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Parker et al [114] found that dedicated bicycle lanes significantly increased the ridership rate in New Orleans, and the same was true for a new town in Singapore [115]. However, Yamamoto and Talvitie [116] noted that most Asian cities do not have a significant length of dedicated bicycle lanes or pathways, although there has been some experience with this approach in China, Singapore, Malaysia, and the resort town of Cha am in Thailand [117,118]. It is hoped that enhanced safety due to dedicated bike lanes (Figure 9) would lead to greater ridership, but it seems that bicycle ownership within Nava Nakorn would need to increase for the positive environmental benefits to be realized.…”
Section: The Themes That Guided the Designmentioning
confidence: 99%
“…Parker et al [114] found that dedicated bicycle lanes significantly increased the ridership rate in New Orleans, and the same was true for a new town in Singapore [115]. However, Yamamoto and Talvitie [116] noted that most Asian cities do not have a significant length of dedicated bicycle lanes or pathways, although there has been some experience with this approach in China, Singapore, Malaysia, and the resort town of Cha am in Thailand [117,118]. It is hoped that enhanced safety due to dedicated bike lanes (Figure 9) would lead to greater ridership, but it seems that bicycle ownership within Nava Nakorn would need to increase for the positive environmental benefits to be realized.…”
Section: The Themes That Guided the Designmentioning
confidence: 99%
“…It is critical because of the success or the failures will determine his future political career path towards highest political position, the Presidency. During the gubernatorial campaign, Joko Widodo emphasized his program into six: (1) Education subsidy through 'Kartu Jakarta Pintar, KJP' (Smart Jakarta Card), (2) Citizens Healthcare by introducing 'Kartu Jakarta Sehat, KJS' (Healthy Jakarta Card) and (3) Gradually minimizing flooding problems (4) Promoting excellent public transportation system by strengthening Busway system, developing monorail system and Jakarta Mass Rapid Transit System, (5) Bureaucracy reform by improving services to the Citizens (6) Slums upgrading and street vendors management. The problem of street vendors in Tanah Abang area was very desperate.…”
Section: Block G Tanah Abang Jakarta Casementioning
confidence: 99%